The Capability of Raman Microspectroscopy to Differentiate Printing Inks. Issue 1 (24th May 2017) - Johnson, Chelsea E.; Martin, Paul; Roberts, Katherine A.; Trejos, Tatiana; Corzo, Ruthmara; Almirall, Jose R.; Safer, Alan M.
Abstract: This study applies Raman microspectroscopy to differentiate the chemical components in printing inks of different brands, colors, and type using the 532 nm and 785 nm excitation wavelengths. Spectra were collected from 319 inks (78 inkjet, 76 toner, 79 offset, and 86 intaglio) representing various colors. Comparisons were performed to calculate discrimination capability percentages for each ink type. Overall, Raman microspectroscopy differentiates according to the following hierarchy: intaglio (96%), inkjet (92%), offset (90%), and toner (61%). The ability of Raman microspectroscopy to differentiate between same‐colored inks from different brands was dependent on the color and ink analyzed. Based on ink color, the discrimination capability ranged from 75 to 94% (inkjet), 0 to 86% (toner), and 0 to 77% (offset). Copper phthalocyanine was detected in cyan inks and various intaglio inks, while carbon black was identified in black inkjet, offset, and intaglio inks.